Preoperative anemia and extensive transfusion during stay-in-hospital are critical for patient`s mortality: A retrospective multicenter cohort study of oncological patients undergoing radical cystectomy. Issue 6 (December 2018) - Ceanga, Andreea-Iuliana; Ceanga, Mihai; Eveslage, Maria; Herrmann, Edwin; Fischer, Dania; Haferkamp, Axel; Wittmann, Maria; Müller, Stefan; Van Aken, Hugo; Steinbicker, Andrea Ulrike
Abstract: Background: Preoperative anemia and allogeneic blood transfusions (ABTs) may affect outcomes in cancer surgery. The prevalence of anemia, the use of ABTs, the risks of transfusions, lengths of stay and mortality of oncological patients undergoing radical cystectomy were investigated in three University Hospitals in Germany. Patients and Methods: Hospital records of 220 consecutive patients undergoing radical cystectomy from 2010 to 2012 were retrospectively analyzed for independent risk factors of ABT and unfavorable outcomes (readmission, increased length of stay (LOS) or death) using multivariate regression analysis. Results: Preoperative anemia was present in 40%. 70% of patients received blood transfusions. Low preoperative and intraoperative nadir hemoglobin levels were associated with receipt of ABT (OR 1.33, P = 0.04 and OR 2.94, P < 0.001 respectively). Transfusion of ten or more red blood cell units (RBCs) during the entire hospital stay was a predictor of an increased LOS (P < 0.001) and death (OR 52, 95%CI [5.9, 461.3], P < 0.001), compared to non-transfused patients. Preoperative ABT and ASA scores were associated with ≥10RBCs. Conclusion: Anemic patients undergoing radical cystectomy had a high risk to receive ABTs. Preoperative transfusions and transfusion of ≥10RBCs during the entire hospital stay may increase patient`s mortality. Prospective, randomized controlled studies have to follow this study.